Dal pensiero pratico al pensiero discorsivo: il caso del discorso politico - Gargani, David (Rivista Italiana di Filosofia del Linguaggio, 2012)
The use of cognitive approaches for treating the philosophy of language has had the merit of reconnecting culture, understood as a system of signs, to our direct, perceptual/motor experience of the external world. The knowing subject, and his bio-cognitive apparatus and conceptualizations based on his direct interaction with the world, has returned to the center of our attention. However, this theory carries with it a certain risk: that of conflating reflective thought, along with its most advanced cultural productions, the fruit of the collective elaboration of entire societies and traditions, with the initial products of individual experience. Many experiential and embodied theories of cognition admit the role of language in shaping higher cognition, as is the case for Lakoff’s theory of political thought. Nevertheless, this theory in some way weakens the importance of language and of explicit, argumentative discourse, in the construction and, in particular, and in the representation of ideologies. These observations bring us to the problem of the relationship between thought and language, between concepts and meanings. We propose a synthesis between an experiential-semantic cognitive view and theories of language formativity, showing how practical thought, based on direct experience, turns into discursive thought that is available to consciousness, and how discursive practice can be used to develop the critical thinking that is the basis of democracy.